KONTRIBUSI MODEL SIMULASI TIK UNTUK MENUMBUHKAN KEAKTIFAN BELAJAR PESERTA DIDIK - Suprobo, Hendarti; Andi Prastowo; Chairul Bariyah; Syarifah Risma Aulia; Tiara Yuliarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Not providing opportunities for students to participate actively in learning because the learning process is one-way and focuses on cognitive, resulting in students being less active during or in learning activities. Based on this problem, this research aims to find out whether the ICT-based simulation learning model can contribute to the activeness of class IV SD/MI students in learning. The type of research used is descriptive qualitative with a case study method. Data was collected through interviews and sources relevant to this research. Then the data is reduced, presented, and conclusions are drawn. The results of this study show that ICT-based simulation models can contribute to active student learning. The results that can be seen in each indicator of student learning activity include: students actively participate in carrying out the tasks given by forming groups, actively asking questions, actively talking with other people or discussing, actively looking for information related to the material given to act out, and Students are actively involved in problem solving in the form of appropriate role distribution and are able to assess their abilities.